Practical Solutions for On-Farm Management of Soil & Water - Gouveia, Gregory (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Dr. Gregory Gouveia, Lectures- Soil Science, University of the West Indies